Odpowiedź :
y=s(x)
a,b - składniki
a +b= 100
s= a kw + b kw
s(a,b) = a kw +b kw
s(a) = a kw + (100 - a) kw
s(a) = 2a kw - 200 a + 1000
a= 2
b= -200
c= 1000
delta= 40000- 4* 2*1000
delta= 40000- 8000
delta=3200
Aw= - (-200)/ 4
Aw= 50
100-50= 50
a,b - składniki
a +b= 100
s= a kw + b kw
s(a,b) = a kw +b kw
s(a) = a kw + (100 - a) kw
s(a) = 2a kw - 200 a + 1000
a= 2
b= -200
c= 1000
delta= 40000- 4* 2*1000
delta= 40000- 8000
delta=3200
Aw= - (-200)/ 4
Aw= 50
100-50= 50
100
/ \
64 36
64[kwadrat] = 4096
36[kwadrat] = 1296
f=8[kwadrat] + 2*12 + 12
/ \
64 36
64[kwadrat] = 4096
36[kwadrat] = 1296
f=8[kwadrat] + 2*12 + 12